Including Everyone, Everywhere: Understanding Opportunities and Challenges of Geographic Gender-Inclusion in OSS - Artha Azriadi Prana, Gede; Ford, Denae; Rastogi, Ayushi; Lo, David; Purandare, Rahul; Nagappan, Nachiappan (ICSE 2022, 2021)
The gender gap is a significant concern facing the software industry as the development becomes more geographically distributed. Widely shared reports indicate that gender differences may be specific to each country. However, how complete can these reports be with little to no research reflective of the Open Source Software (OSS) process and communities software is now commonly developed in? Our study presents a multi-region geographical analysis of gender inclusion on GitHub. This mixed-methods approach includes quantitatively investigating differences in gender inclusion in projects across geographic regions and investigate these trends over time using data from contributions to 21,456 project repositories. We also qualitatively understand the unique experiences of developers contributing to these projects through strategically targeted surveys. Our findings indicate that there are statistically significant differences in gender diversity between regions. Since 2014, there has been a small and statistically significant improvement of gender diversity among software project contributors in Northern America and South-Eastern Asia but negligible change elsewhere. We also find that most motivations and barriers to contributions (e.g. lack of resources to contribute and poor working environment) were shared across regions, however, some insightful differences, such as how to make projects more inclusive, did arise. From these findings, we derive and present implications for tools that can foster inclusion in open source software communities and empower contributions from everyone, everywhere.